Chromogranin B Purification for Condensate Formation and Client Partitioning Assays In Vitro - Anup Parchure; Julia von Blume (Bio-Protocol)
Chromogranin B and other members of the granin protein family form condensates that recruit clients like proinsulin. The condensation in the lumen of trans-Golgi network (TGN) is critical for the biogenesis of secretory granules. Here, we describe a protocol to purify the tagged version of chromogranin B close to its native form at the TGN, which can then be utilized for microscopy-based assays to monitor condensate formation in vitro and client partitioning depending on the material properties of chromogranin B assemblies.